Episiotomy rate in Vietnamese-born women in Australia: support for a change in obstetric practice in Viet Nam - Anh T Trinh; Amina Khambalia; Amanda Ampt; Jonathan M Morris; Christine L Roberts (The World Health Organization, 2013)
OBJECTIVE: To describe the use of episiotomy among Vietnamese-born women in Australia, including risk factors for, and pregnancy outcomes associated with, episiotomy. METHODS: This population-based, retrospective cohort study included data on 598 305 singleton, term (i.e. > 37 weeks' gestation) and vertex-presenting vaginal births between 2001 and 2010. Data were obtained from linked, validated, population-level birth and hospitalization data sets. Contingency tables and multivariate analysis were used to compare risk factors and pregnancy outcomes in women who did or did not have an episiotomy. FINDINGS: The episiotomy rate in 12 208 Vietnamese-born women was 29.9%, compared with 15.1% in Australian-born women. Among Vietnamese-born women, those who had an episiotomy were significantly more likely than those who did not to be primiparous, give birth in a private hospital, have induced labour or undergo instrumental delivery. In these women, having an episiotomy was associated with postpartum haemorrhage (adjusted odds ratio, aOR: 1.26; 95% confidence interval, CI: 1.08-1.46) and postnatal hospitalization for more than 4 days (aOR: 1.14; 95% CI: 1.00-1.29). Among multiparous women only, episiotomy was positively associated with a third- or fourth-degree perineal tear (aOR: 2.00; 95% CI: 1.31-3.06); in contrast, among primiparous women the association was negative (aOR: 0.47; 95% CI: 0.37-0.60). CONCLUSION: Episiotomy was performed in far fewer Vietnamese-born women giving birth in Australia than in Viet Nam, where more than 85% undergo the procedure, and was not associated with adverse outcomes. A lower episiotomy rate should be achievable in Viet Nam.